Targeted delivery of RNAi to cancer cells using RNA-ligand displaying exosome - Nasir Uddin; Daniel W. Binzel; Dan Shu; Tian-Min Fu; Peixuan Guo (Elsevier, 2023)
Exosome is an excellent vesicle for in vivo delivery of therapeutics, including RNAi and chemical drugs. The extremely high efficiency in cancer regression can partly be attributed to its fusion mechanism in delivering therapeutics to cytosol without endosome trapping. However, being composed of a lipid-bilayer membrane without specific recognition capacity for aimed-cells, the entry into nonspecific cells can lead to potential side-effects and toxicity. Applying engineering approaches for targeting-capacity to deliver therapeutics to specific cells is desirable. Techniques with chemical modification in vitro and genetic engineering in cells have been reported to decorate exosomes with targeting ligands. RNA nanoparticles have been used to harbor tumor-specific ligands displayed on exosome surface. The negative charge reduces nonspecific binding to vital cells with negatively charged lipid-membrane due to the electrostatic repulsion, thus lowering the side-effect and toxicity. In this review, we focus on the uniqueness of RNA nanoparticles for exosome surface display of chemical ligands, small peptides or RNA aptamers, for specific cancer targeting to deliver anticancer therapeutics, highlighting recent advances in targeted delivery of siRNA and miRNA that overcomes the previous RNAi delivery roadblocks. Proper understanding of exosome engineering with RNA nanotechnology promises efficient therapies for a wide range of cancer subtypes.